2015
DOI: 10.1007/s12192-015-0618-8
|View full text |Cite
|
Sign up to set email alerts
|

The detection and role of heat shock protein 70 in various nondisease conditions and disease conditions: a literature review

Abstract: As an intracellular polypeptide, heat shock protein 70 (HSP70) can be exposed on the plasma membrane and/or released into the circulation. However, the role of HSP70 in various nondisease and disease conditions remains unknown. Quantitative methods for the detection of HSP70 have been used in clinical studies, revealing that an increase in circulating HSP70 is associated with various types of exercise, elderly patients presenting with inflammation, mobile phones, inflammation, sepsis, chronic obstructive pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 85 publications
2
67
0
3
Order By: Relevance
“…Heat‐shock proteins (Hsps) are molecular chaperones that can be up‐regulated when cells are exposed to different kinds of stressors. It has been demonstrated that 72 kDa, the major inducible Hsp70 protein, possesses antagonistic actions, depending on its localization . While intracellular Hsp70 exerts a powerful protective and anti‐inflammatory effect, extracellular Hsp70 (eHsp70) is considered as one of the DAMPs and therefore might be able to activate innate and inflammatory responses .…”
Section: Introductionmentioning
confidence: 99%
“…Heat‐shock proteins (Hsps) are molecular chaperones that can be up‐regulated when cells are exposed to different kinds of stressors. It has been demonstrated that 72 kDa, the major inducible Hsp70 protein, possesses antagonistic actions, depending on its localization . While intracellular Hsp70 exerts a powerful protective and anti‐inflammatory effect, extracellular Hsp70 (eHsp70) is considered as one of the DAMPs and therefore might be able to activate innate and inflammatory responses .…”
Section: Introductionmentioning
confidence: 99%
“…Among the members of HSPs, HSP70 (HSPA) ubiquitously exists in unstressed cells and functions as an ATP-dependent molecular chaperone for the assistance of folding newly synthesized proteins, and the translocation of proteins into the different cellular compartments [7-10]. Accumulating evidence indicates potent effects of HSP70 toward various diseases, such as cancer, infection and autoimmune diseases [4, 11]. Since the increase of HSP70 protein expression is reportedly related to poor outcome [12], it is currently considered that inhibition of HSP70 could become one of therapeutic targets against these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock proteins help to protect cells from a wide array of stresses like elevated temperature and infection [28]. As an intracellular polypeptide, Hsp 70 can be exposed on the plasma membrane and/or released into the circulation [29,30]. A wide array of cellular functions has been attributed to HSC 70, mostly through its cooperation with co-chaperones.…”
Section: Discussionmentioning
confidence: 99%